The wolves [large type] - Berenson, Alex (Berenson, Alex. John Wells novel., 2016)
John Wells has just barely managed to stop an operation designed to drive the United States and Iran into war, but the instigator himself disappeared behind an impenetrable war of security. Now it's time for him to pay, and Wells has made it his personal mission.